2014
DOI: 10.1016/j.molimm.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of B cells to lupus pathogenesis

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of autoantibodies. This review summarizes first the results obtained in the mouse that have revealed how B cell tolerance is breached in SLE. We then review the B cell subsets, in addition to the autoAb producing cells, which contribute to SLE pathogenesis, focusing on marginal zone B cells, B-1 cells and regulatory B cells. Finally, we review the interactions between B cells and other immune cells that have been implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 177 publications
2
34
0
2
Order By: Relevance
“…Kes., Ph.D., Apt, Faculty of Pharmacy, Universitas Airlangga, 4 -6 Airlangga Road, Surabaya -6 0115, Indonesia. E-mail: junaidi-k@ff.unair.ac.id be shedded in the circulation become the memory T cells 9,10 . The low number of L-selectin in the spleen will increase the lupus severity since the high number of T effector, some of them are autoreactive, cannot be handled results in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Kes., Ph.D., Apt, Faculty of Pharmacy, Universitas Airlangga, 4 -6 Airlangga Road, Surabaya -6 0115, Indonesia. E-mail: junaidi-k@ff.unair.ac.id be shedded in the circulation become the memory T cells 9,10 . The low number of L-selectin in the spleen will increase the lupus severity since the high number of T effector, some of them are autoreactive, cannot be handled results in inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…These autoantibodies form pathogenic immune complexes that deposit into organs, ultimately inducing inflammation and tissue damage (Cancro et al, 2009;Sang et al, 2014). Many of the current therapeutic options for the treatment of SLE include antimalarial agents, nonsteroidal anti-inflammatory drugs, glucocorticoids, and immunosuppressive drugs, which all seek to reduce the autoimmune inflammatory process but also can result in general immunosuppression and toxicity (Tsokos, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on murine models revealed abnormal signaling mechanisms through B lymphocytes, with the AKT/mTOR pathway playing an essential role [19,20]. The gene analysis of signaling molecules specific for B lymphocytes identified two inhibitor receptors, Lyn and CD22, which are critical in the regulation of B lymphocyte phenotype expressed in SLE.…”
Section: B Lymphocyte Signalingmentioning
confidence: 99%